ASEM as an Example of Broad Cooperation Framework Between Europe and Asia - Jankowiak, Anna H.; Mazurek, Szymon (ASEM jako przykład ogólnoramowej współpracy między Europą a Azją, 2010)
The increasing importance of Asia and the Pacific region in global economy has shown that the mutual relations between Asia and Europe are crucial for both sides. The rivalry between the regions gave way to a multi-faceted cooperation and agreements. An example of a forum for regular cooperation and experience sharing is Asia-Europe Meeting (ASEM) that serves the function of an informal dialogue among the Asian and European countries. This article presents ASEM as a forum for establishment of multidimensional relations of the interregional nature.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 71-79
Keywords: cooperation; multidimensional relations; institutionalization of economic cooperation